Circular RNAs are abundantly expressed and upregulated during repair of the damaged endometrium by Wharton’s jelly-derived mesenchymal stem cells - Sun, Baolan (Stem Cell Res Ther, 2018)
BACKGROUND: Wharton’s jelly-derived mesenchymal stem cells (WJ-MSCs) exhibit strong and powerful potential in repairing different diseases. The expression profile of circular RNA (circRNA) provides valuable insight for regulation of the repair process and exploration of reparative effect mechanisms. METHODS: Human endometrial stromal cells (ESCs) were cultured with mifepristone to obtain damaged ESCs, which were then cocultured with or without WJ-MSCs (cocultured group versus non-cocultured group) to observe the reparative effect upon damaged ESCs by WJ-MSCs. CircRNA microarray was performed between the two groups. Based on the transcriptomics data, the differential gene expression profiles of the two groups were analyzed by Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, and network analysis methods. Screening of a circRNA database was performed, and the results were confirmed by quantitative polymerase chain reaction (qPCR). RESULTS: WJ-MSCs exerted a reparative effect upon damaged ESCs in the cocultured group such as improved cell morphology, higher proliferative ability, and lower apoptosis rate. CircRNA array showed that 7757 circRNAs were differentially expressed in ESCs from the cocultured group. Mitotic cell cycle, cell cycle process, and nuclear division ranked top in the GO upregulated list of the two groups, while DNA replication and cell cycle ranked top in the KEGG pathway analysis upregulated list of the two groups. The nine most aberrantly expressed circRNAs were selected for further verification in the same cohort of samples by microarray analysis. Seven of the nine most aberrantly circRNAs were confirmed to be significantly upregulated in the cocultured group. And four of the seven circRNAs (hsa_circ_0015825, hsa-circRNA4049-38, hsa-circRNA5028-15, and hsa_circ_0111659) expression both in ESCs and WJ-MSCs tended to decrease with time by qPCR. The levels of the remaining three circRNAs (hsa-circRNA8881-21, hsa_circ_0020492 and hsa_circ_ 0026141) did not change significantly over time in either ESCs or WJ-MSCs. Moreover, we focused on hsa_circRNA_0111659 and predicted its miRNAs and targeted mRNA. The association of circRNA-miRNA-mRNA is likely to be involved in regulating the repair of endometrial damage. CONCLUSIONS: Our results presented the abundant and upregulated circRNAs profile during repair of the damaged endometrium by WJ-MSCs and provided a novel perspective for circRNAs in the regulation of WJ-MSCs for endometrial repair. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13287-018-1046-3) contains supplementary material, which is available to authorized users.